Rapid authentication of leather and leather products - Mirghani, Mohamed Elwathig Saeed; Mohd. Salleh, Hamzah; Che Man, Yakoob; Jaswir, Irwandi (American-Eurasian Network for Scientific Information (AENSI), 2012)
Recent discovery of such products being sold to the public without clear description of its status has prompted Muslims and other religious groups to be more sensitive in choosing these items. Because of this concern, it is crucial to develop methods of detection for halal and/or kosher products. In this study two analytical techniques for determination of pigskin leather were conducted. Leather products from different origins including cow, goat, sheep and pig were used. Scanning Electron Microscope (SEM) was used to identify the characteristics of pigskin leather as source of non-halal leather based on the grain surface and cross section of leather samples. Fourier transform infrared (FTIR) spectroscopy was used to obtain mid IR spectra at wavenumber region of 4000 cm-1 to 400 cm-1. The differentiation between leather types and non-halal leather from FTIR analysis was based on three regions of interest from the spectra obtained, which are 1200-1000 cm-1, 700-600 cm-1 and 500-400 cm-1. These regions can be proposed as a standard for leather determination especially for non-halal leather and leather products. The study showed that the techniques developed are rapid, reliable, accurate and convenient to authenticate leather products made from pigskin or skin of other animal species. The result of this study could also be used to distinguish between leather and non-leather or imitation leather products.